Rancangan Model Penilaian Kesiapan Implementasi Vendor Managed Inventory di PT XYZ - Wiwis Undariyanto; Senator Nur Bahagia (Program Studi Teknik Industri, Fakultas Teknologi Industri, Institut Teknologi Bandung, 2023)
Vendor Managed Inventory (VMI) is one of collaboration strategy in the supply chain to optimize the availability of goods with minimal costs for both collaborating parties. PT XYZ as buyer company has adopted the VMI concept in providing fuel oil and has benefited from assured availability. To obtain more benefits, the company needs to expand the scope of VMI implementation to provide the other goods needed by the company. The absence of tools to assess the readiness to implement VMI for a product has become one of the obstacles to its implementation for other types of goods. Previous research has developed a readiness assessment model for a company to implement VMI. However, this assessment model is not comprehensive as it only evaluate readiness from the perspective of one party. In addition, what products can be managed with the VMI system in a company has not been answered. These two things are research gaps for developing a model for assessing the readiness of implementing VMI for a product for buyer company and supplier. To address these gaps, this research designs an assessment model for the readiness of VMI implementation by developing a reference model through PLS-SEM analysis and confirmatory factor analysis approach. This research produced two VMI readiness assessment instruments, one intended for buyer company consisting of 2 dimensions, 8 elements and 21 indicators and the other for supplier consisting of 2 dimensions, 7 elements and 15 indicators. The results of testing assessment instruments on three products used by the company indicate that the proposed instruments from this research can be used to determine the readiness of VMI implementation within the company.